Aqueous Dispersion of Carbon Nanomaterials with Cellulose Nanocrystals: An Investigation of Molecular Interactions. Issue 37 (28th July 2022) - Aramfard, Mohammad; Kaynan, Ozge; Hosseini, Ehsan; Zakertabrizi, Mohammad; Pérez, Lisa M.; Asadi, Amir
Abstract: Dispersing carbon nanomaterials in solvents is effective in transferring their significant mechanical and functional properties to polymers and nanocomposites. However, poor dispersion of carbon nanomaterials impedes exploiting their full potential in nanocomposites. Cellulose nanocrystals (CNCs) are promising for dispersing and stabilizing pristine carbon nanotubes (pCNTs) and graphene nanoplatelets (pGnP) in protic media without functionalization. Here, the underlying mechanisms at the molecular level are investigated between CNC and pCNT/pGnP that stabilize their dispersion in polar solvents. Based on the spectroscopy and microscopy characterization of CNCpCNT/pGnP and density functional theory (DFT) calculations, an additional intermolecular mechanism is proposed between CNC and pCNT/pGnP that forms carbonoxygen covalent bonds between hydroxyl end groups of CNCs and the defected sites of pCNTs/pGnPs preventing re‐agglomeration in polar solvents. This work's findings indicate that the CNC‐assisted process enables new capabilities in harnessing nanostructures at the molecular level and tailoring the performance of nanocomposites at higher length scales. Abstract : Cellulose nanocrystals (CNCs) prove promising for dispersing and stabilizing pristine carbon nanotubes (pCNTs) and graphene nanoplatelets (pGnP) in polar solvents. Herein, the dispersion mechanism of CNCpCNT/pGnP is explained by experimental and computational outcomes. The results indicate that carbon–oxygen covalent bonds form between hydroxyl end groups of CNC and defected sites pCNT/pGnP preventing re‐agglomeration in polar solvents.